Sternal fractures: "Operative treatment" should be kept in mind - Banu Yoldas; Hidir Esme; Mustafa Calik (Journal of Research in Medical Sciences, 2012)
Isolated sternal fracture is a benign condition which generally heals with conservative treatment. But sometimes surgical intervention is necessary due to pain, other organ injury and union problems. There are several ways for repair; however, the best method is not yet defined. In this report, we presented two cases who were treated surgically for different indications with different suture materials. When anatomically correction can be achieved, using suture materials is a safe and effective method.